Missing words: causes, symptoms and solutions for middle school students’ reading anxiety - Onur ER (Humanities & Social Sciences Communications)
Abstract The objective of this study is to identify the causes, symptoms, and strategies to reduce reading anxiety based on the perspectives of Turkish language teachers and middle school students with high levels of reading anxiety (MSHRAs). Adopting a qualitatively driven design, this study is a quantitatively supported qualitative research. Quantitative data were only used to select participants. In this context, the Reading Anxiety Scale was used to identify students with high levels of reading anxiety. Based on the results of the scale, Turkish language teachers who had high levels of reading anxiety in their classrooms were selected for the study. Data was collected in middle schools in two districts of Düzce province, Türkiye, during the 2024-2025 academic year. Qualitative data were gathered from nine Turkish language teachers and 13 MSHRAs chosen through criterion sampling. The researcher utilised semi-structured interview forms to collect this qualitative data. Furthermore, a document analysis was performed, examining 26 exam papers as part of this investigation. The study’s findings reveal that reading anxiety is influenced by factors such as fear of making mistakes while reading aloud, poor reading skills, peer bullying, and classroom practices like competitive reading activities. Emotional symptoms, including shyness, fear, and low self-confidence, alongside behavioural symptoms, such as avoidance behaviours, were identified as key indicators of reading anxiety. Both Turkish language teachers and MSHRAs suggested strategies to reduce reading anxiety, including tailored reading activities, creating a supportive classroom environment, encouraging parental involvement, and visualising exam questions to ease assessment-related anxiety.